Female business owners pay higher interest rates on corporate loans - Alessandro Tang-Andersen Martinello; Bjarke Mønsted; Rastin Matin; Sigurd Anders Muus Steffensen; Karen Holm Laursen (Danmarks Nationalbank, 2021)
We analyze micro-level data from the Danish credit register and find that female business owners pay higher interest rates on corporate loans than male owners. The gender gap is partly explained by differences in firm and loan characteristics. However, an economically and statistically significant gap persists even after flexible machine learning techniques are applied to the data. While the gender gap most likely arises during the negotiation process, we do not find that it depends on market power or the extent to which banks use data-driven approaches to determine interest rates.
Keywords: G21; J16; 330; Financial sector; changes in interest rates; credit risk; statistical methods